THE INFLUENCE OF PROMOTION, PRICE AND SERVICE QUALITY ON ONLINE PURCHASE DECISIONS - Ningtiyas, Febriana; sukaris, sukaris (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2021)
Currently, in the digitalization era, there are many changes in people’s lifestyles who tend to use gadgets and have activities in cyberspace such as shopping online or in other terms called e-commerce. The development of online shopping platforms in Indonesia currently has many choices such as Lazada, Tokopedia, OLX, Bukalapak and Shopee. The development of Indonesian e-commerce competition in the second quarter of 2021, Shopee was ranked first in Indonesia with 93.4 million users, so Shopee has become an application that is often used by many Indonesians. Many factors influence why people shop online, including the price factor, promotion of service quality. This study aims to determine the effect of promotion, price and service quality on online purchasing decisions. the population in this study were students of the University of Muhamadiyah Gresik, Faculty of Economics and Business Class 2018. The sample in this study was 100 students, while the online shopping platform chosen was shopee.co.id users. Data was taken using a questionnaire through an online survey which was measured by a Likert scale. The data obtained were analyzed using multiple linear regression analysis techniques, which were then tested with a partial test. The results of this study indicate that the promotion variable has a significant effect on online purchasing decisions at Shopee.co.id with Sig Data was taken using a questionnaire through an online survey which was measured by a Likert scale. The data obtained were analyzed using multiple linear regression analysis techniques, which were then tested with a partial test. The results of this study indicate that the promotion variable has a significant effect on online purchasing decisions at Shopee.co.id with Sig Data was taken using a questionnaire through an online survey which was measured by a Likert scale. The data obtained were analyzed using multiple linear regression analysis techniques, which were then tested with a partial test. The results of this study indicate that the promotion variable has a significant effect on online purchasing decisions at Shopee.co.id with Sig0.030 < 0.05. Price nosignificant effect on online purchasing decisions at Shopee.co.id with Sig 0.243 > 0.05. Service qualitysignificant effect on online purchasing decisions at Shopee.co.id with Sig of 0.001 < 0.05